Posterior reversible encephalopathy syndrome secondary to steriod resistant nephrotic syndrome in a child - Osman Yeşilbaş; Hasan Serdar Kıhtır; Mey Talip Petmezci; Seda Balkaya; Meryem Benzer; Canan Hasbal Akkuş; Figen Bakırtaş Palabıyık; Esra Şevketoğlu (Van Tıp Dergisi, 2019)
................................................................................................................................